Identifying resonances of the Galactic bar in Gaia DR2: I. Clues from action space. Issue 2 (27th October 2020) - Trick, Wilma H; Fragkoudi, Francesca; Hunt, Jason A S; Mackereth, J Ted; White, Simon D M
ABSTRACT: Action space synthesizes the orbital information of stars and is well suited to analyse the rich kinematic substructure of the disc in the second Gaia data release's radial velocity sample. We revisit the strong perturbation induced in the Milky Way disc by an m  = 2 bar, using test particle simulations and the actions ( JR, Lz, Jz ) estimated in an axisymmetric potential. These make three useful diagnostics cleanly visible. (1) We use the well-known characteristic flip from outward to inward motion at the outer Lindblad resonance (OLR; l  = +1, m  = 2), which occurs along the axisymmetric resonance line (ARL) in ( Lz, JR ), to identify in the Gaia action data three candidates for the bar's OLR and pattern speed Ωbar : 1.85Ω0, 1.20Ω0, and 1.63Ω0 (with ∼0.1Ω0 systematic uncertainty). The Gaia data is therefore consistent with both slow and fast bar models in the literature, but disagrees with recent measurements of ∼1.45Ω0 . (2) For the first time, we demonstrate that bar resonances – especially the OLR – cause a gradient in vertical action 〈 Jz 〉 with Lz around the ARL via ' Jz -sorting' of stars. This could contribute to the observed coupling of 〈 vR 〉 and 〈| vz |〉 in the Galactic disc. (3) We confirm prior results that the behaviour of resonant orbits is well approximated by scattering and oscillation in ( Lz, JR ) along a slope Δ JR /Δ Lz  = l / m centred on the l : m ARL. Overall, we demonstrate that axisymmetrically estimated actions are a powerful diagnostic tool even in non-axisymmetric systems.